Kepemimpinan Islam: Perspektif Sejarah Dakwah Islam - Rs., Syamsudin (Prophetica, 2009)
Islamic leadership history is eternal discrepancy history among sollens wreck, namely fair politics leadership democratic, and sein s wreck, namely fair kepemiminan performing and democratic. Pasca is Rasulullah Saws term. best friends memeberikan samples berkenaan with model or fair penegakan kepemiminan pattern it. Best of all no five modelyang can be adapted: namely current support with conceptual resistance, passive resistance, social control via resuscitation action, statement, and collaboration that konstruktif Meanwhile justice and trust is two essential qualities as requisite of boss and Islam governances.Keywordsi:Kepemimpinan Islam, Sejarah Dakwah Islam